Innovative Strategies in Curriculum Management to Prepare Future Human Resources - Anco, Anco (International Journal of Transdisciplinary Knowledge, 2024)
Education plays a crucial role in preparing competent human resources (HR) in the era of globalization and the Fourth Industrial Revolution. Innovative curriculum management is one of the key strategies in responding to the changing dynamics of the workforce. This literature review aims to analyze various innovative strategies in curriculum management that have been implemented in different educational institutions to prepare graduates who are adaptive, creative, and equipped with 21st-century skills. The findings indicate that technology-based approaches, project-based learning (PBL), and the integration of soft skills and hard skills are the key factors in curriculum reform.